Bilingualism and Code-Switching in Indonesia’s Alpha Generation: A Case Study of El Barack and Sekala Bumi - Noveintine, Dhanesvar Karel (Crises on Languages and Literature, 2026)
This study explores the use of Indonesian and English among Alpha generations which focuses on two children namely El Barack Alexander and Dia Sekala Bumi. These children, attending international primary schools, have been exposed to English from an early age. This study aims to understand their proficiency in both languages and how they apply both of them. This study analyzes the children's utterances from YouTube and TikTok videos to assess their language proficiency and code-switching behavior based on the sociolinguistics and bilingualism theories. The findings reveal that both children demonstrate fluent bilingualism with natural code-switching and a diverse vocabulary in both languages. Their bilingual abilities are influenced by their family, school environment, and exposure to digital media. The study highlights the growing trend of bilingualism among Alpha generations and its implications for language development and communication. El Barack and Sekala's language use provides valuable insights into the developing linguistic scope of Alpha generation. This study underlines the importance of bilingualism in a globalized world and its impact on cognitive and social development.